MITIGATION OF COPPER-INDUCED TOXICITY IN WISTAR RATS' SERUM BIOCHEMICAL PROFILE BY CANNABIS LEAF EXTRACT (FUDMA JOURNAL OF SCIENCES, 2025)
Copper serves as an integral part of specialized cuproproteins responsible for normal growth and development of the body, and excess accumulation in the body has a detrimental effect. Anthropogenic influences and an increased number of vehicles coupled with intensive urban and rural infrastructure result in the accumulation of heavy metals in the soil and plants, which are subsequently transmitted to humans via the food chain. The study was designed to provide positive effects of cannabis, establish a means of preventing copper exposure, and devise a means of preventing them. The aim of the study was to determine the therapeutic effect of cannabis leaf extract on copper-induced toxicity and serum biochemical profile changes. The experimental study was carried out using 20 Wistar rats allocated into 4 groups containing 5 rats each: group A (negative control), group B (copper only), group C (cannabis only), and group D (copper then treated with cannabis). The results showed decreased serum electrolytes (urea, bicarbonate, creatinine, total protein, albumin, bilirubin, AST, and ALP) and increased serum ALT and erythropoietin, which were later reversed after treatment with cannabis. In conclusion, cannabis leaf extract has therapeutic effects on copper toxicity.
Keywords: Cannabis; Copper; Serum Biochemistry; Wistar Rat